Women and work in Malaysia: negotiating the private and public place - Rokis, Rohaiza (Institut Sosial Malaysia, 2005)
Malaysia is a fast becoming a modern, industrial nation with multinational and global interests, thus one would expect modern thinking to be influencing Malaysia society today. However, the effect of globalisation has a slow effect on some women in Malaysia. In the areas of work and home, cultural traditions have significantly affected women's lives. Working women in Malaysia face a conflicting situation between the need to participate in employment and the need to conform to the cultural expectations on women's responsibilities at home. The theme of this paper is about paradoxical duality. It discusses the paradoxical situations of the private and public place, which most working women experience in life. Specifically, it explains the paradoxical clash of modernisation of the country with the conservative practice of the nation, which frequently mistreats women. This paper attempts to understand how cultural traditions penetrate into women's life in Malaysia. It elaborates the influence of religions and cultural traditions of women's lives. This eventually creates a paradoxical image and a clashing position of women in public and private space.